Preschool Children with Gender Normative and Gender Non-Normative Peer Preferences: Psychosocial and Environmental Correlates - Martin, Carol Lynn (2012)
We addressed several issues concerning children who show gender non-normative (GNN) patterns of peer play. First, do young children with GNN peer preferences differ from children with gender normative (GN) peer preferences in problem behaviors? Second, do GNN and GN children differ in sociability and isolation and do they have differential socialization opportunities with externalizing, internalizing, and socially competent peers? We employed a Bayesian approach for classifying children as GNN based on their peer preferences as compared to their peers using a sample of Head Start preschool children from a large Southwestern city (N = 257; 53% boys; M age = 51 months; 66% Mexican American). To calculate socialization opportunities, we assessed affiliation to each child in the class and weighted that by each peer’s characteristics to determine the exposure that each child had to different kinds of peers. GN children of both sexes interacted more with same-sex peers, which may limit learning of different styles of interaction. As compared to GN children, GNN children exhibited more engagement in other-sex activities and with other-sex play partners and GNN children experienced somewhat fewer peer interactions, but did not differ on problem behaviors or social competence. Boys with GNN peer preferences had increased exposure to peers with problem behaviors. GNN girls experienced little exposure to peers with problem behaviors, but they also had little exposure to socially competent peers, which may reduce learning social skills from peers. Implications of these findings for future socialization and development will be discussed.